“La educación es importante”: Socio-educational experiences and gender dynamics among young mothers attending college - Alvarado, Beatriz (Cuestiones de Género: de la igualdad y la diferencia, 2013)
Childcare is already a difficult job, which can become even more stressful if other responsibilities are added. This article describes educational and social experiences of low- income women who are mothers and first-generation college students in both private and public educational institutions in Peru and Mexico. These women are not only responsible for their children’s well-being, but also struggle to maintain their status as regular full-time students. Four main themes are analyzed in this study: Familiar participation in the childcare, school pressure and educational system support, socio-cultural beliefs about women’s roles and childcare, and participants’ views of their professional and social futures. The author suggests that more attention needs to be provide to these women´s socio-educational needs, for them to attain their goals in an already unfriendly patriarchal societal context.